A novel arsenic methyltransferase gene of Westerdykella aurantiaca isolated from arsenic contaminated soil: phylogenetic, physiological, and biochemical studies and its role in arsenic bioremediation. Issue 3 (18th January 2016) - Verma, Shikha; Verma, Pankaj Kumar; Meher, Alok Kumar; Dwivedi, Sanjay; Bansiwal, Amit Kumar; Pande, Veena; Srivastava, Pankaj Kumar; Verma, Praveen Chandra; Tripathi, Rudra Deo; Chakrabarty, Debasis
Abstract : The study explores new insights into the arsenic metabolism by WaarsM and provides a potential approach for the bioremediation process. Abstract : Elevated arsenic concentration in the environment and agricultural soil is a serious concern to crop production and human health. Among different detoxification mechanisms, the methylation of arsenic is a widespread phenomenon in nature. A number of microorganisms are able to methylate arsenic, but less is known about the arsenic metabolism in fungi. We identified a novel arsenic methyltransferase ( WaarsM ) gene from a soil fungus, Westerdykella aurantiaca . WaarsM showed sequence homology with all known arsenic methyltransferases having three conserved SAM binding motifs. The expression of WaarsM enhanced arsenic resistance in E. coli (Δ ars ) and S. cerevisiae (Δ acr2 ) strains by biomethylation and required endogenous reductants, preferably GSH, for methyltransferase activity. The purified WaarsM catalyzes the production of methylated arsenicals from both AsIII and AsV, and also displays AsV reductase activity. It displayed higher methyltransferase activity and lower K M 0.1945 ± 0.021 mM and K M 0.4034 ± 0.078 mM for AsIII and AsV, respectively. S. cerevisiae (Δ acr2 ) cells expressing WaarsM produced 2.2 ppm volatile arsenic and 0.64 ppm DMA(v ) with 0.58 ppm volatile arsenicals when exposed to 20 ppm AsV and 2 ppm AsIII, respectively. Arsenic tolerance in rice after co-culture with genetically engineered yeast suggested its potential role in arsenic bioremediation. Thus, characterization of WaarsM provides a potential strategy to reduce arsenic concentration in soil with reduced arsenic accumulation in crops grown in arsenic contaminated areas, and thereby alleviating human health risks.